Analisis Pengaruh Perencanaan Pajak, Kepemilikan Manajerial, Ukuran Kap terhadap Manajemen Laba - Kazhadiva, Rivialdo; Wiyono, Slamet (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study addresses the issue of detecting earnings management practices in infrastructure companies influenced by various factors. Against this background, the author aims to examine the relationship between the variables of tax planning and managerial ownership on earnings management as the dependent variable. The analytical method used is multiple linear regression with purposive sampling technique. The data used in this study is secondary data derived from the annual reports of infrastructure companies listed on the Indonesia Stock Exchange for the period of 2021-2023. The results of the study indicate that the tax planning variable has a positive effect on earnings management, while the managerial ownership and company size variables have a negative effect on earnings management.